(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Chronic kidney disease mineral bone disorder is a metabolic bone disease present in almost all uremic patients. The aim of this research to indicate the stage of chronic kidney disease (CKD) that affect the bone metabolism that leading to the mineral and hormonal imbalance by studying the relationship among osteocalcin , glomerular filtration rate (GFR), parathyroid hormone, calcium and phosphorus levels in the blood. Method: The study included 52 patients with predialysis chronic kidney disease stage 3-5 and 40 apparently healthy relatives accompanying the patients. Glomerular filtration rate (GFR) was calculated for each patient. Renal function tests, including serum levels of urea, creatinine, a biochemical marker of bone metabolism: osteocalcin (OSN), calcium, phosphorus, and parathyroid hormone (PTH), were measured for each participant. Results: Serum urea and creatinine levels were significantly higher in CKD patients Than that of apparently healthy control. There is significantly higher serum parathyroid hormone, serum phosphorus, serum osteocalcin (P<0.01, P<0.01, P<0.01 respectively) in CKD patients than that of the healthy control group. While low serum calcium level in CKD patients as compared to the corresponding group (P<0.01). Conclusion: Hyperphosphatemia and hypocalcemia in the end stage of predialysis CKD patients lead to increase parathyroid hormone secretion, which causes high bone turnover characterized by significantly high serum osteocalcin in these patients. Parathyroid hormone and osteocalcin were used as a biomarker for the development of bone and mineral disorders in predialysis CKD patients.